The Effect of Adipose-Derived Stem Cells on Wound Healing: Comparison of Methods of Application - Hyeonwoo Kim; Mi Ri Hyun; Sang Wha Kim (Stem Cells International)
Impaired wound healing is a significant medical problem. Recently, cell-based therapy focused on stem cells has been developed to overcome the challenges of defective wound healing. In this study, we aimed to evaluate the effectiveness of adipose-derived stem cells (ASCs) in promoting wound healing, using different techniques for administering them. Dorsal full-thickness skin defects (1×1 cm) were created in three groups of mice that received intravenous ASCs by intravenous injection, intramuscular injection, and topical application, respectively. Three control groups received saline in the same ways. Wound healing was assessed clinically, wounds were examined histologically, and GFP-labelled ASCs were detected with an IVIS imaging system. The results revealed that ASCs accelerated wound healing independent of their mode of administration. Histological examination showed that the ASCs accelerated reepithelialization, and IVIS analysis indicated that many ASCs were present in the wound area and disappeared after wound healing.